Incidence and aetiology of a raised hemidiaphragm after cardiopulmonary bypass. - Large, S R (1985)
A raised hemidiaphragm has been reported as an uncommon complication of cardiopulmonary bypass, possibly resulting from cold injury to the phrenic nerve. At Papworth Hospital myocardial protection during cardiac arrest relies in part on irrigation of the pericardial cavity with large volumes of Hartmann's solution at 4 degrees C. Retrospective review of the chest radiographs of 100 consecutive patients undergoing cardiopulmonary bypass showed that 31 had a raised left hemidiaphragm soon after operation. The only significant correlation was with aortic cross clamp time (p less than 0.03). A prospective study of 36 consecutive patients undergoing cardiopulmonary bypass was then undertaken with diaphragmatic screening and chest radiography. Preoperative screening gave normal results in all patients. In the early postoperative period 16 (44%) had left diaphragmatic weakness or paralysis, two (5.5%) right sided weakness, and two (5.5%) bilateral weakness. Repeat screening of these patients showed resolution in all but four cases (80%) at six months and in all but two (90%) at one year. The greater number of left sided lesions than of right (8:1) is probably due to the fact that the cold jet of irrigating fluid is directed towards the left phrenic nerve. These findings have implications with regard to the optimum temperature of the irrigant fluid for myocardial protection during cardiopulmonary bypass.